The Correlation between Students’ Satisfaction with E-learning and Their English Achievement - Mercy Myshall Rellely; Virginia Gabrella Sengkey (Universitas Dian Nuswantoro, 2022)
Abstract. This research aimed to find out the correlation between students’ satisfaction with e-learning and their English achievement. This was a quantitative study that used descriptive and correlational research designs. The instruments used in this study were a questionnaire adopted from Liaw (2007) and the students’ final English class grades. Seventy-nine 11th-grade students enrolled at one of the private high schools in North Sulawesi in the first semester of the academic year 2020/2021 participated in this study. It was found that the students were satisfied with e-learning (M=3.48) and their English achievement was very good (M=91.62). Regarding the correlation between the two variables, a significant correlation was found between students’ satisfaction with e-learning and their English achievement with p=.000 < 0.005, r=.441. Thus, teachers should always ensure that students are satisfied with their e-learning so that their English achievement can also be maximized.Keywords: e-learning, English achievement, students’ satisfactionAbstrak. Penelitian ini bertujuan untuk mengetahui hubungan antara kepuasan siswa dengan e-learning dan pencapaian bahasa Inggris mereka. Penelitian ini merupakan penelitian kuantitatif dengan desain penelitian deskriptif dan korelasional. Instrumen yang digunakan dalam penelitian ini adalah angket yang diadopsi dari Liaw (2007) dan nilai akhir siswa di kelas Bahasa Inggris. Responden dari penelitian ini adalah 79 siswa kelas XI yang terdaftar di salah satu SMA Swasta di Sulawesi Utara pada semester I tahun ajaran 2020/2021. Hasil yang diperoleh adalah siswa puas dengan e-learning (M=3,48) dan prestasi bahasa Inggris mereka sangat baik (M=91,62). Berkenaan dengan korelasi antara kedua variabel, ditemukan korelasi yang signifikan antara kepuasan siswa dengan e-learning dan prestasi bahasa Inggris mereka dengan p=.000 < 0.005, r=.441. Oleh karena itu, guru perlu selalu memastikan bahwa siswa puas dengan e-learning mereka sehingga pencapaian bahasa Inggris mereka juga dapat maksimal.Kata kunci: e-learning, kepuasan siswa, pencapaian bahasa Inggris